Immigration, 'race' and ethnicity in contemporary France - Hargreaves, Alec G. (Routledge, 1995)
Immigration is one of the most significant and pressing issues in contemporary France. This is the first comprehensive survey to be published in English covering developments in this field during the last twenty years.